Answer:
yes, that is very correct
Step-by-step explanation:
yes
Answer:
(7, 0), (-8, 0), (0, 0)
Step-by-step explanation:
y = f(x) = 0
the real solutions are the ones that cross the x-axis because when a point is on the x-axis, its y coordinate will be 0.
=> (7, 0), (-8, 0), (0, 0)
Answer:
(x-3)(x^2-7) = x^3 -3x^2 -7x + 21
just change the sign of the root and put x in front of it, then multiply the factors all together
(x-3)(x-sqr7)(x+sqr7) roots come in conjugate pairs to eliminate irrational coefficients
(x-sqr7)(x+sqr7) = x^2-7. similar to (a-b)(a+b) = a^2-b^2
Step-by-step explanation: